Coaching And Mentoring Among Sisc+: Their Roles And Responsibilities, Successes And Challenges, And Their Influences Towards The Teaching And Learning Of The Teachers - Mastura binti Kamaruddin
Transforming the nation's educational systems requires a big task that is an intervention to the education system itself Malaysia Education Blueprint (2013- 2025) was reformed to empower and bring national education up to the international level. One of the initiatives is the district transformation program (DTP) in which School Improvement Specialist Coaches (SISC+) was appointed and had been positioned full-time at District Education Offices (PPD) to coach and mentor the teachers in their districts. The aim of this study was to elucidate the coaching and mentoring that directly link instructional coaching with improved teacher performance or student achievement in Rembau, Jempol Jelebu and Kuala Pilah districts in Negeri Sembilan since coaching and mentoring is a new approach in Malaysian education system. It is a mixed method approach while the selected design is a case study and roped in three SISC+ and 3 of their coaches for interview while 55 respondents participated in questionnaires. Data were collected through semi-structured interviews, observations, document analysis, and survey and were analysed and guided by Braun and Clarke's (2006) six-step thematic analysis with the help of ATLAS. ti and SPSS is also employed for the quantitative method. For the first research question, it is found that the roles and responsibilities of SISC+ are to help and share their knowledge with the coachees as well as provide 21''century teaching and learning knowledge to the teacher through professional development and professional learning community. The study revealed that, their successes were measured through being accepted by their coachees in improving both the lesson quality and knowledge growth while working with adult learners with different attitude is one of their toughest challenges besides having conflicting roles. As for the influence of SISC+, the findings revealed that the SISC+ has been successful in influencing the coachees to transform in the improvement of lesson quality. Based on the results, there were implications on the enactment of policies, conceptual development and practical implementation to the stakeholders and the SISC+. This study also has paved the ways for more related research in the future. It was concluded that the initiative of the Ministry to accelerate the transformation of education through positioning the SISC+ in PPD is a good effort however these SISC+ must be trained to be competent, knowledgeable and skillful in the areas of pedagogies, curriculum, and assessments. On the whole understanding the roles of a coach at the educational setting are crucial at all level then only these SISC+ can perform their duty well.